KONTRIBUSI KEKUATAN OTOT LENGAN DAN KESEIMBANGAN BADAN TERHADAP KEMAMPUAN SERVIS ATAS BOLAVOLI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN JASMANI, KESEHATAN DAN REKREASI STKIP PARIS BARANTAI KOTABARU - ARHAM SYAHBAN (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
This study aims to determine the contribution of the arm muscle strength and balance of the body the ability of a service on volleyball on students of Physical Education, Health and Recreation STKIP Paris barantai Kotabaru. The method used is descriptive method with data collection using test and measurement techniques of the arm muscle strength and balance of the body as well as the contribution of each of the top volleyball servicing capabilities. The study population was a student STKIP Paris Barantai. The population of the entire male student health physical education and recreation totaled 87 people. For samples taken as many as 30 people using samples of simple random sampling method. The survey results revealed no contribution arm muscle strength (X1) on the ability of the service on volleyball (Y) of 17.8%. There is contributing the balance of the body (X2) on the ability of the service on volleyball (Y) of 14.3%. No contribution arm muscle strength (X1), and the balance of the body (X2) together on the ability of the service on volleyball (Y) by 33%. Keywords: Arm Muscle Strength, Balance Board, Serviceability Top volleyball